The Differential Risk of Intraoperative Floppy Iris Syndrome (IFIS) with Tamsulosin versus Other α1-Adrenergic Antagonists: A Systematic Review and Comparative Meta-Analysis - Muhammad Adithia; Boy Tri Janpiter; Ashabul Anhar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: α1-adrenergic antagonists are a cornerstone therapy for lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH). Their association with intraoperative floppy iris syndrome (IFIS) during cataract surgery is well-established, yet the comparative risk between the highly α1A-selective agent tamsulosin and other α1-blockers has not been adequately quantified in a meta-analysis. This study aimed to synthesize the evidence to determine the magnitude of this differential risk. Methods: Following PRISMA guidelines, a systematic search was conducted across PubMed, Embase, Scopus, and the Cochrane Library through September 2025. We included comparative studies reporting IFIS incidence in adults on α1-blockers undergoing cataract surgery. Data were independently extracted by two reviewers. The primary outcome was the pooled Odds Ratio (OR) for IFIS, calculated using a random-effects model. Heterogeneity was assessed with the I² statistic. Results: The search yielded 1,218 records, with six studies comprising 10,878 patients meeting the inclusion criteria. The incidence of IFIS was 18.7% in the tamsulosin group versus 2.9% in the comparator group (other α1-blockers or control). Tamsulosin was associated with a significantly greater risk of IFIS (Pooled OR = 4.28, 95% CI: 2.91–6.31, p < 0.00001). This corresponds to an absolute risk increase of 15.8% and a Number Needed to Harm (NNH) of 7, suggesting one additional case of IFIS occurs for every seven patients treated with tamsulosin instead of a different agent. Moderate heterogeneity was noted (I² = 62%). Conclusion: This meta-analysis provides robust evidence that tamsulosin carries a more than four-fold increased odds of IFIS compared to other α1-blockers. This substantial and clinically meaningful risk, highlighted by an NNH of 7, mandates a risk-stratified approach to BPH management. A patient's present or future ophthalmological needs must be a central factor in the shared decision-making process when selecting an α1-blocker.